Risk factors and newborn outcomes associated with maternal deaths in the UK from 2009 to 2013: a national case–control study - Nair, M; Knight, M; Kurinczuk, J (Wiley, 2016)
Objectives To identify the risk factors for and adverse newborn outcomes associated with maternal deaths from direct and indirect causes in the UK.